Diffraction Pattern Simulation of Crystal Structure towards the Ionic Radius Changes Via Vesta Program - Rini, Ari Sulistyo (Talenta Publisher, 2019)
The Simulations of X-ray diffraction patterns of MgO, BaO and ZnS ceramics were successfully performed by VESTA program, based on the crystal structures visualization. The aim of this research was to obtain the relationship between ionic radius to the diffraction pattern. The X-ray diffraction pattern was generated from visualization of the crystal structure. The crystal structure information was obtained from JCPDS data which contained lattice parameter, atomic coordinate and the space group. The X-ray diffraction pattern parameters which are taken into account in this research are diffraction angle of 2 Theta and Intensity. The results indicated that the peak position and intensity of the diffraction pattern are influenced by ionic radius of the cations. Structural transformation was also detected from this simulation.